(untitled) (Journal of actual problems of jurisprudence, 2019)
This article covers the issues on judges training system. It is also paid attention to theprofessional activities and knowledge of judges. A comparative and legal analysis has been investigated regarding with experience of foreign judges. Famous scholars’ and lawyers’ points of view are also mentioned taking into account national court system of the country. Key words: judicial authorities, the status of judges, justice,Biy’s court, judicial acts.